2016
DOI: 10.1016/j.socscimed.2016.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Distinct age and self-rated health crossover mortality effects for African Americans: Evidence from a national cohort study

Abstract: The predictive effects of age and self-rated health (SRH) on all-cause mortality are known to differ across race and ethnic groups. African American adults have higher mortality rates than Whites at younger ages, but this mortality disparity diminishes with advancing age and may “crossover” at about 75 to 80 years of age, when African Americans may show lower mortality rates. This pattern of findings reflects a lower overall association between age and mortality for African Americans than for Whites, and healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Most Medicare beneficiaries are ≥65 years of age; consequently, the mortality rate is high in this population. 7,8 One-third of CVD events among Medicare beneficiaries are fatal. 19 The hospital discharge diagnosis method has been used previously to define fatal MI and stroke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most Medicare beneficiaries are ≥65 years of age; consequently, the mortality rate is high in this population. 7,8 One-third of CVD events among Medicare beneficiaries are fatal. 19 The hospital discharge diagnosis method has been used previously to define fatal MI and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Many analyses of Medicare claims data have investigated CVD as an outcome, but have relied on hospital discharge diagnoses and discharge disposition (ie, deceased or alive), an approach that fails to capture out‐of‐hospital CVD deaths and some in‐hospital CVD deaths . In 2013, 84% of Medicare beneficiaries were ≥65 years of age, and mortality is high in this population . Not having cause of death for Medicare beneficiaries can result in the inability to accurately estimate CVD event rates, as many events are fatal, and in biased exposure‐outcome associations due to censoring some CVD‐related deaths as nonevents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that the effect of the socio-economic status on SRH can be partially accounted for by lifestyle and psychological factors (16). Other factors that correlate with SRH are ethnic origin (17,18), place of residence (19) and the experience of single motherhood (20).…”
Section: Introductionmentioning
confidence: 99%
“…Despite on the adjustment on demographic indicators, estimation (self-estimation) of health, health status, mortality rates from all causes were significantly lower in African-American race than in those people with the white race. In older ages (75-80 years), race performance in African American individuals may be reduced [24].…”
mentioning
confidence: 99%